The Effects of Principal’s Leadership and Educational Quality on Teacher’s Performance - Irawati, Elvira; Ahyani, Nur; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2022)
This study aimed at examining the influence of principal’s leadership and educational quality on teacher’s performance, both partially and concurrently. This study was carried out at all of Prabumulih City's private junior high schools. The study was conducted during August and October of 2021, with 46 teachers as respondent. The questionnaire was used to collect data. Both principal’s leadership and educational quality have an impact on the success of Prabumulih's private junior high school instructors. The novelty in this study, where we could have good performance of teacher, it needs good leadership. This study contributes to more have attention the principal’s leadership and educational quality where we will have good reputation of teacher’s performance.